CONCEPT AND APPLICATION OF AKAD WAKALAH IN MURABAHA FINANCING IN ISLAMIC BANKING (A COMPARATIVE STUDY BETWEEN INDONESIA AND MALAYSIA) - Bagya Agung Prabowo; Jasri Bin Jamal (Fakultas Hukum, Universitas Diponegoro, 2017)
Islamic banks have grown stronger by continuing to provide innovative products and services to successfully increase the number of customers. So far, the majority of financing by Islamic banks controlled by murabaha financing almost 80% - 95%. In the bank's murabaha scheme as the seller (ba’i) to purchase necessary items and then resell it to customers, clients (musytari) with a sales price equivalent to the purchase price and profitability of banks. In reality, Islamic banks using wakalah empower customers to purchase their goods. Step wakalah apply concepts to customers is unwise because MUI Fatwa No.04 / DSN-MUI / IV / 2000 has determined that the sale of murabaha contracts made after the goods become the property of Islamic banking principles. The main problem in Indonesia is that there are legal provisions that are not in harmony and not based on actual consumer rights. It is geared toward legal uncertainty. To overcome various problems, this research adopted the method of analysis based on doctrinal content, by implementing four types of approaches to the law, namely: (i) history / historical; (ii) Jurisprudence / philosophy; (iii) comparison; and (iv) analytical and critical. In addition, harmonized approach is also necessary for legislative alignment with Islamic philosophy and the philosophy of consumer protection. By making Malaysia as a reference, this thesis aims to identify the application wakalah perspective and consumer protection improvement in Indonesia. In addition to this, the restructuring of the existing system in Indonesia is required by legislation harmony, improvement and diversification of institutional oversight mechanisms Islamic banking operations